2014
DOI: 10.1513/annalsats.201310-346oc
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Responses to Rhinovirus- and Influenza-associated Pulmonary Exacerbations in Patients with Cystic Fibrosis

Abstract: Rationale: The mechanism by which viruses cause exacerbations of chronic airway disease and the capacity of patients with cystic fibrosis (CF) to respond to viral infection are not precisely known.Objectives: To determine the antiviral response to infection in patients with CF.Methods: Sputum was collected from patients with CF with respiratory exacerbation. Viruses were detected in multiplex polymerase chain reaction (PCR)-based assays. Gene expression of 84 antiviral response genes was measured, using a focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…exacerbations associated with rhinovirus and influenza virus with virus-negative specimens which showed that viruses were associated with immune responses tailored to specific infections [19]. In our study, we showed that rhinovirus was the most prevalent virus.…”
Section: Discussionsupporting
confidence: 50%
“…exacerbations associated with rhinovirus and influenza virus with virus-negative specimens which showed that viruses were associated with immune responses tailored to specific infections [19]. In our study, we showed that rhinovirus was the most prevalent virus.…”
Section: Discussionsupporting
confidence: 50%
“…All these viruses are inducing distinct pathogenesis in the lung and it is therefore conceivable that the mechanisms of virus-induced CF exacerbation are at least in part virus-specific. In line with this hypothesis, a recent study by Ramirez et al demonstrated that CF exacerbations triggered by RV or influenza virus led to a distinct antiviral response [37]. Therefore, it would be interesting to test our in vitro system with other clinically relevant respiratory viruses such as influenza and respiratory syncytial virus.…”
Section: Smentioning
confidence: 67%
“…Although 50% of exacerbations were associated with a viral respiratory tract infection, viral infections had no acute effect on changes in P. aeruginosa sputum bacterial density. Given the significance of CF exacerbations, further work is needed to determine if viral infections elicit an immune response that leads to exacerbation that may be independent of P. aeruginosa bacterial load in CF patients [29]. As well, further investigation is required to understand the etiology of exacerbations in patients who do not have viral infections, since increased P. aeruginosa bacterial density in sputum does not appear to be responsible.…”
Section: Resultsmentioning
confidence: 99%